Effect of errors on miss distance of missile trackers in active decoy environment - Edury Vijaya lakshmi; N. N. Sastry; B. Prabhakar Rao (Institute of Advanced Engineering and Science, 2019)
Lock on missiles are a major threat to vital installations. Soft kill solutions against lock on incoming missiles such as deployment of active decoys can be very effective to war of threat. The weaknesses in onboard missile tracking radars can be gainfully used to increase the miss distance between target and the missile. The effect of geometrical positioning errors of two horn monopulse missile mounted radars has been analyzed in this paper. As so gain differences between the two horns can cause variations in the miss distance. This aspect has also been studied. The variation of miss distance with jammer power to signal ratio (J/S) is also presented. It can be seen that the miss distance is always midway between the target and the decoy. Random angular positioning errors of the missile radar have been analyzed and it is found that the miss distance increases with increase of angular errors.